Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 199538 by cherokeesay last updated on 04/Nov/23

Answered by mr W last updated on 05/Nov/23

a)  f(x)=x^3 −1−m(x−1)  f′(x)=3x^2 −m=0  x^3 −1−3x^2 (x−1)=0  2x^3 −3x^2 +1=0  (x−1)^2 (2x+1)=0  ⇒x=1 ⇒m=3  ⇒x=−(1/2) ⇒m=(3/4)  b)  m=3  f(x)=x^3 −1−3(x−1)=(x−1)^2 (x+2)  zeros at x=−2, x=1  ...  c)  ∫_(−2) ^1 (x^3 −3x+2)dx  =(1/4)(1^4 −2^4 )−(3/2)(1^2 −2^2 )+2(1+2)=((27)/4)

a)f(x)=x31m(x1)f(x)=3x2m=0x313x2(x1)=02x33x2+1=0(x1)2(2x+1)=0x=1m=3x=12m=34b)m=3f(x)=x313(x1)=(x1)2(x+2)zerosatx=2,x=1...c)21(x33x+2)dx=14(1424)32(1222)+2(1+2)=274

Commented by mr W last updated on 05/Nov/23

Commented by cherokeesay last updated on 05/Nov/23

thank you so much master !!!

thankyousomuchmaster!!!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com